Leading Public Design: How Managers Engage with Design to Transform Public Governance - Christian Bason (Copenhagen Business School (CBS), 2017)
In recent years, design has emerged as an approach to shaping public policies and services across industrialized and emerging economies. International institutions, national and local governments, foundations, philanthropies, volunteer and community organizations, and educational institutions at all levels have taken up a variety of approaches inspired by the field of design, often in response to growing pressures to innovate. But how these approaches influence public innovation – how they change the roles of public managers, how they help managers generate new ideas and solutions – and whether, as some have suggested, they might signal the rise of new governance models or paradigms – these issues have not, with perhaps a few exceptions, been rigorously explored. In this thesis, I explore these issues by examining the experiences of public managers who have pioneered the use of design approaches. More specifically, I confront three questions: Characterizing design practice: Within public sector organizations, what does the application of design approaches entail? Why do public managers look to and commission design, and what tools, techniques, processes and methods are brought into play? Design as change catalyst: How do design approaches, if at all, influence how public managers engage with their problems and opportunities for innovation? To what extent do design approaches help public managers achieve the changes they are striving for, and why? Emerging forms of public governance: What form and shape do the outputs resulting from design approaches take? What are the links between design approaches and the emergence of new types of public solutions and governance models?
hdl:10398/9480
Keywords: 650